Infections and inequalities: The modern plagues / Paul Farmer - Farmer, Paul (California: University of California Press, 1998)
Su texto nos ilustra cómo las fuer- zas que determinan que un indivi- duo visite o esté lejos de un doctor, y todos los procesos que definen la salud
1. The vitality of practice: On personal trajectories 2.The persistent plagues
Incluye Índice
Col. Med
Keywords: 1. THE CONSUMPTION OF THE POOR 2. THE CASE OF RURAL HAITI